Psychological mechanisms of disinformation and their impact on social polarization - Lewandowski, Piotr (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2024)
This article examines the complex relationship between disinformation activities and the rise of social polarization. The study identifies the main psychological mechanisms through which disinformation exerts its impact and explores their connection to factors shaping polarizing social attitudes. The article conceptualizes the key disinformation factors that contribute to social polarization. By integrating research perspectives from social psychology and social research on communication, polarization, and disinformation, cognitive mechanisms are applied to the field of security sciences. Artykuł analizuje złożone relacje między działaniami dezinformacyjnymi a wzrostem polaryzacji społecznej. Badanie zakłada identyfikację głównych mechanizmów psychologicznego oddziaływania dezinformacji oraz ich odniesienie do czynników kształtujących polaryzacyjne postawy społeczne. Artykuł dokonuje konceptualizacji czynników dezinformacyjnych oddziałujących na polaryzację społeczną. Poprzez integrację perspektyw badawczych pochodzących z nurtu psychologii społecznej i badań społecznych nad komunikacją, polaryzacją i dezinformacją następuje przeniesienie operatów poznawczych na grunt nauk o bezpieczeństwie.
Psychologiczne mechanizmy oddziaływania dezinformacji na polaryzację społeczną
Keywords: disinformation; information security; international security; social polarization; dezinformacja; bezpieczeństwo informacyjne; bezpieczeństwo międzynarodowe; polaryzacja społeczna